2007
DOI: 10.1080/00365520701320513
|View full text |Cite
|
Sign up to set email alerts
|

Fecal pyruvate kinase: A potential new marker for intestinal inflammation in children with inflammatory bowel disease

Abstract: The measurement of stool PK could be a potentially useful marker of IBD activity in children. However, its clinical value demands further studies for comparison with other tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…Czub and colleagues demonstrated that the dimeric isoform of pyruvate kinase (PK) detected in the stool of children suffering from inflammatory bowel disease (IBD) might serve as a potential non-invasive screening tool for inflamed pouch mucosa. 42 Enzyme immunoreactivity was found to be significantly higher in all IBD patients than in healthy subjects. 42 Lower activity of plasma PK of autistic children could therefore be inversely related to the higher fecal level.…”
Section: Disclosuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Czub and colleagues demonstrated that the dimeric isoform of pyruvate kinase (PK) detected in the stool of children suffering from inflammatory bowel disease (IBD) might serve as a potential non-invasive screening tool for inflamed pouch mucosa. 42 Enzyme immunoreactivity was found to be significantly higher in all IBD patients than in healthy subjects. 42 Lower activity of plasma PK of autistic children could therefore be inversely related to the higher fecal level.…”
Section: Disclosuresmentioning
confidence: 99%
“…42 Enzyme immunoreactivity was found to be significantly higher in all IBD patients than in healthy subjects. 42 Lower activity of plasma PK of autistic children could therefore be inversely related to the higher fecal level.…”
Section: Disclosuresmentioning
confidence: 99%
“…16 The aim of this study was therefore to investigate measurement of fecal M2-PK in the differentiation of functional and organic bowel disorders.…”
mentioning
confidence: 99%
“…Low M 2 -PK expression could potentially mean flare-up resolution. Czub et al 52 reported abnormal M 2 -PK levels in 49 of 75 UC patients and in 27 of 32 CD patients. Though in later studies, they were not able to demonstrate superiority in differentiating disease severity and remission compared with FC.…”
Section: A Marker Of Inflammatory Bowel Diseasementioning
confidence: 99%